PENGARUH EFIKASI DIRI TERHADAP KINERJA DENGAN DUKUNGAN ORGANISASIONAL SEBAGAI PEMODERASI - Saraswati, A.A.Ayu Ngr. Dinni; Dewi, I.G.A. Manuati; Piartini, Putu Saroyeni (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
To realize service which is with quality needed by self-confidence level of officer in working which later will influence yielded performance. Besides officer self-confidence level, support of organization also very needed to reach expected performance so that will realize excellent service. This research aim to explain influence self efficacy to performance, and know role of organizational support as moderating at influence of self efficacy to performance. Research conducted in Office Land of Gianyar Sub- Province with a population of 155 employees. The sample is determined by purposive sampling as many 90 employees who were directly involved in the process of land services. Technique analyse data the used are descriptive and regretion moderating assisted with program SPSS Version 22 for Windows. Result of research find that self efficacy have an effect on positive at officer performance. Effect of support moderating of organizational to performance is also found by significant with the meaning support of organizational can moderating influence of self efficacy to officer performance.
Keywords: Self-Efficacy, Organizational Support, and Performance